GENDER SELF CONCEPT OF ATHLETES OF THE CITY ANÁPOLIS - GO (Fiep Bulletin - online, 2013)
The study's aim was to identify, through the self-concept, the gender stereotype of athletes from the city of Anapolis in the modalities of dance, fight, swimming, basketball, futsal. The population studied, in the city of Anapolis-Go, were athletes of both sexes from the modalities of dance, fight, swimming, basketball, futsal. With an average age of 18 to 34 years. It was randomly composed by 84 individuals being 34 female and 50 male from the cited modalities. The questionnaires used were the Feminine Inventory of the Self-Concept's Gender Schemas (IFEGA) for female athletes and the Male Inventory of the Self-Concept's Gender Schemas (IMEGA) for male athletes. For the data analysis was performed a descriptive analysis and percentage. It was used the Kruskal Wallis T test using a SPSS19.0 program adopting the significance level of p ? 0.005. As a result the study found that male athletes are considered 46% male Heteroschematic, 18% are considered female Heteroschematic and 36% are classified as Isoschematic. For female athletes, 11.8% are male Heteroschematic, 32.4% are Isoschematic, and already 55.9%, are considered female Heteroschematic. When analyzed for individual sport it was found that 24.4% are male heteroschematic, 37.8% female heteroschematic and 37.8% isoschematic. However in team sports 30.8% are considered isoschematic, 41.0% are male heteroschematic and 28.2% female heteroschematic. The study concludes that most males were classified as male heteroschematic and most females were female heteroschematic. As for individual sports they were considered female heteroschematic and isoschematic, as for the team sports most were classified as male heteroschematic.
Keywords: self-concept; gender; athletes.